SASAK TRADITIONAL VILLAGES: A TOURISM POTENTIAL AND CONSERVATION EFFORT FOR CULTURE AND PLANTS - Sujarwo, Wawan (P2KK LIPI, 2019)
In the millennial era, social-community conditions that have become increasingly urbanised have resulted in the loss of original roots. For some communities, the loss of their culture can be articulated by a loss of identity. One of the efforts to preserve culture and plants is to preserve and sustain traditional villages and encourage government programs to increase the number of traditional villages to be declared as ?Tourism Traditional Villages?. This study aims to unravel the tourism potential of seven Sasak traditional villages related to traditional buildings, art performances, plant usage, and other economic potentials that could be created. The study was conducted by visiting and interviewing local residents in seven Sasak traditional villages on Lombok Island in Indonesia. The results of the study indicated that tourism traditional villages can provide many tangible benefits, which can be felt directly by villagers, such as employment or additional income, and intangible benefits, e.g. preservation of local culture, including cultural and plant knowledge. Traditional villages can also provide resilience and independence for their people to be a source of food, especially for vegetables and fruits, so they do not depend so much on the availability of consumer goods in traditional markets, which are subject to price fluctuations.